The Analysis of Fiber Content of Nuggets and Crackers With the Basic Ingredients of Kepok Banana Hump (Musa paradisiaca Var. Balbisina Colla) - Rifatul Ridlo; Sugeng Maryanto; Riva Mustika Anugrah (JURNAL GIZI DAN KESEHATAN, 2021)
Nugget and crackers are fast foods that are widely consumed and favored by the public, usually used as dishes or snacks. Banana tubers is a local food commodities which contains of high fiber can be processed as an ingredients nuggets and crackers. The purpose ofthis reseach was to determine the fiber content of nuggets and crackers with the basic ingredients of kepok banana hump (Musa paradisiaca Var. Balbisina Colla). This study was experimental design. The nugget formulation consisted of 3 comparisons, the ratio of banana hump : wheat flour (25%: 75%) (F1), (50%: 50%) (F2), and (75%: 25%) (F3). The cracker formulation consists of 3 comparisons, the ratios of banana hump: tapioca flour (25%: 75%) (F1), (50%: 50%) (F2), and (75%: 25%) (F3). Test the fiber containt by the gravimatry method which is then described. The results in this study was analyzed of the fiber value of nuggets and crackers kepok banana hump every (100g). The highest fiber content of nuggets was F3: 0.514g, F2: 0.322g and F1: 0.186g. The highest fiber content of Kepok banana hump crackers is F3: 0.861g, F2: 0.747g and F1: 0.727g. The fiber value of the kepok banana hump crackers is higher than the kepok banana hump nugget.